Phagocytosis of Gut Bacteria by Entamoeba histolytica - Lakshmi Rani Iyer; Anil Kumar Verma; Jaishree Paul; Alok Bhattacharya (Frontiers in Cellular and Infection Microbiology, 2019)
The protist parasite Entamoeba histolytica causes amoebiasis, a major public health problem in developing countries. Only a small fraction of patients infected with the parasite display invasive disease involving colon or extra intestinal tissues such as liver. E. histolytica exists as two distinct forms, cysts, the infective form, and trophozoites, that are responsible for disease pathology. The latter multiply in the large intestine occasionally causing disease. The large intestine in humans is populated by a number of different bacterial communities and amoebic cells grow in their midst using some as food material. Several studies have shown relationship between bacteria and E. histolytica growth and virulence. However, an understanding of this relationship in human gut environment is not clear. We have investigated the possibility that there may be specific interaction of amoeba with different bacteria present in the gut environment by using a metagenomic pipe line. This was done by incubating bacteria isolated from human fecal material with E. histolytica and then identifying the bacterial population isolated from amoebic cells using a rRNA based metagenomic approach. Our results show that the parasite prefers a few bacterial species. One of these species is Lactobacillus ruminus which has never shown to be associated with E. histolytica.